Evaluation of degradation in chemical compounds of wood in historical buildings using FT-IR and FT-Raman vibrational spectroscopy - Seyed Mahdi Moosavinejad (Maderas. Ciencia y Tecnología, 2019)
Vibrational spectroscopy approaches like FT-IR and FT-Raman, as analytical method, can be used to assess chemical changes in historical wood structures. In this study, wood samples of three historical buildings, in Gorgan, Iran, namely Tekie Estebar, Molla Esmaiel Mosque, and the Esmaieli Buildings were selected. Wood species was determined by their macroscopic characteristics which were hornbeam (Carpinus betulus), oak (Quercus castaneifolia), beech (Fagus orientalis), and elm (Ulmus glabra), as hardwood species, and yew (Taxus baccata) as a softwood species. Also, some samples of oak were collected from northern and southern sides of the Esmaieli Building in order to compare deterioration environmental factors.. The approximate assignment of the experimental bands was completed by comparing. For this purpose, the experimental bands with the calculated band frequencies of cellulose, hemicellulose and lignin. In addition, the reported assignment for softwood and hardwood was used to confirm the vibrational assignments. The results of spectroscopy revealed that biodegradation had occurred in all species. Comparison between the most important vibrational band frequencies related to carbohydrates and lignin in hardwood species suggested that degradation of carbohydrates was greater than lignin, which could be attributed to brown rot and hydrolysis. Reduction of chemical compounds in south oak samples was higher and could be associated with prevailing wind and UV ray in this side. In the only softwood species (yew), because of its highest exposure to frequent raining, deterioration was observed in both carbohydrates and lignin.